A novel preoperative risk score to optimize patient selection for performing concomitant liver resection with cytoreductive surgery/HIPEC. Issue 1 (1st October 2020) - Lee, Rachel M.; Gamboa, Adriana C.; Turgeon, Michael K.; Zaidi, Mohammad Y.; Kimbrough, Charles; Leiting, Jennifer; Grotz, Travis; Lee, Andrew J.; Fournier, Keith; Powers, Benjamin; Dineen, Sean; Baumgartner, Joel M.; et al.
Abstract: Background: While parenchymal hepatic metastases were previously considered a contraindication to cytoreductive surgery (CRS) and heated intraperitoneal chemotherapy (HIPEC), liver resection (LR) is increasingly performed with CRS/HIPEC. Methods: Patients from the US HIPEC Collaborative (2000–2017) with invasive appendiceal or colorectal adenocarcinoma undergoing primary, curative intent CRS/HIPEC with CC0‐1 resection were included. LR was defined as a formal parenchymal resection. Primary endpoints were postoperative complications and overall survival (OS). Results: A total of 658 patients were included. About 83 (15%) underwent LR of colorectal (58%) or invasive appendiceal (42%) metastases. LR patients had more complications (81% vs. 60%; p  = .001), greater number of complications (2.3 vs. 1.5; p  < .001) per patient and required more reoperations (22% vs. 11%; p  = .007) and readmissions (39% vs. 25%; p  = .014) than non‐LR patients. LR patients had decreased OS (2‐year OS 62% vs. 79%, p  < .001), even when accounting for peritoneal carcinomatosis index and histology type. Preoperative factors associated with decreased OS on multivariable analysis in LR patients included age < 60 years (HR, 3.61; 95% CI, 1.10–11.81), colorectal histology (HR, 3.84; 95% CI, 1.69–12.65), and multiple liver tumors (HR, 3.45; 95% CI, 1.21–9.85) (all p  < .05). When assigning one point for each factor, there was an incremental decrease in 2‐year survival as the risk score increased from 0 to 3 (0: 100%; 1: 91%; 2: 58%; 3: 0%). Conclusions: As CRS/HIPEC + LR has become more common, we created a simple risk score to stratify patients considered for CRS/HIPEC + LR. These data aid in striking the balance between an increased perioperative complication profile with the potential for improvement in OS.